Preparation and Characterization of Silver(I) Ethylcellulose Thin Films as Potential Food Packaging Materials. Issue 3 (10th March 2020) - Scarpelli, Francesca; Crispini, Alessandra; Giorno, Eugenia; Marchetti, Fabio; Pettinari, Riccardo; Di Nicola, Corrado; De Santo, Maria Penelope; Fuoco, Erica; Berardi, Riccardo; Alfano, Pasquale; Caputo, Paolino; Policastro, Debora; et al.
Abstract: Ag(I)‐containing ethylcellulose (EC) films suitable as antbacterial packaging materials have been prepared and fully characterized. Different preparation methods, including the use of green casting solvents, are proposed. The Ag(I) acylpyrazolonato complexes, [Ag(Q py, CF3 )(L)], L=benzylimidazole (Bzim) and L=ethylimidazole (EtimH), used as active additives, display different modes of interactions with EC, depending on their structural features. A thorough investigation of the EC liquid‐crystalline lyotropic phase and its changes with the introduction of silver additives, has been conducted, revealing either the inclusion of complex molecules into the inner structure of the EC matrix or their dispersion on its surface. Moreover, the bactericidal activity of the prepared Ag(I) films seems to be related to the interaction between silver additives and the polymeric EC matrix. Indeed, the EC‐2b films show a particularly good performance even with a low silver content, with a relative bacterial killing of about 100 %. Tests for Ag(I) migration have been performed by using three food stimulants under two assay conditions. Low values of silver release are recorded, particularly at low concentration of silver content, in the case of all new prepared Ag(I) films. Abstract : Antimicrobial packaging : Antibacterial films have been prepared by incorporating selected Ag(I) complexes into a biocompatible ethylcellulose polymeric matrix. The films were structurally characterized and tested against Ag(I) release towards three food simulants, proving to be suitable materials for food packaging applications. The bactericidal activity of the Ag(I) films reaches high values of inhibition of bacterial growth on the contact surface, even when low concentration of Ag(I) complexes are present.